Integrating Education for Sustainable Development-Oriented Projects: Challenges and Opportunities from Geography Teachers' Perspectives - Muhammad Arif; Enok Maryani; Mamat Ruhimat; Dede Sugandi; Dina Syaflita; Mona Adria Wirda (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Education for sustainable development (ESD) is appropriately applied in geography education to support learner-centered instruction that is responsive to local changes and challenges. Mapping the implementation of ESD in geography learning is essential, particularly in areas with complex and vulnerable natural and social characteristics—such as coastal regions—in order to foster learning that prepares future generations to address local issues effectively. The aim of this research is to identify the challenges and opportunities in integrating ESD into teaching practices by analyzing its implementation in geography instruction. This research is a case study involving 18 geography teachers from 10 public high schools in Pesisir Selatan Regency, Indonesia. Data collection methods included surveys with both open- and closed-ended questions. The data were analyzed using descriptive analysis and Miles & Huberman’s qualitative data analysis technique. The categorization applied in this study used an adapted version of the Dreyfus and Dreyfus competency model. The results of the study indicate that teachers have limited understanding of ESD and how to implement it effectively. Consequently, teachers’ ability to apply ESD-oriented learning falls into the advanced beginner category. Many teachers still struggle to distinguish between projects that align with ESD principles and those that do not. Therefore, the development of clear and practical guidelines that assist teachers in easily identifying ESD-oriented projects within project-based learning is necessary to optimize the implementation of ESD in geography education